Safety First: Best Practices For Lab Technicians And Nurses In Handling Specimens And Samples (Journal of Namibian Studies : History Politics Culture, 2022)
Ensuring safety in handling specimens and samples is paramount in healthcare settings to prevent exposure to hazards and maintain the well-being of both patients and healthcare workers. This abstract explores the best practices for lab technicians and nurses in handling specimens and samples, focusing on key areas such as hazard identification, personal protective equipment (PPE) usage, safe collection techniques, laboratory processing, storage, disposal, emergency preparedness, communication, collaboration, and regulatory compliance. By implementing these best practices, healthcare facilities can minimize the risk of accidents, contamination, and exposure to infectious agents or hazardous chemicals. This article underscores the importance of a coordinated effort between lab technicians and nurses in upholding safety standards, ultimately contributing to the delivery of high-quality patient care.